2007
DOI: 10.1590/s1517-86922007000600014
|View full text |Cite
|
Sign up to set email alerts
|

Exercício físico em pacientes dialisados

Abstract: Palavras-chave: Doença renal crônica. Exercício físico. Hemodiálise. Sistema cardiovascular. Qualidade de vida. Keywords:Chronic kidney disease. Exercise training. Hemodialysis. Cardiovascular system. Quality of life. RESUMOPacientes portadores de doença renal crônica (DRC) submetidos a tratamento dialítico apresentam alterações físicas e psicoló-gicas que predispõem ao sedentarismo. Nesta população, a prescrição rotineira de exercícios físicos não é uma prática freqüente, especialmente no nosso país. No entan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
27

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 46 publications
1
17
0
27
Order By: Relevance
“…Those authors have justified their findings due to the small size of the sample and lack of routine physical exercise programs in dialysis centers, which can also explain some results of the research. On the other hand, Reboredo et al (2007) 10 have found a significant improvement in the "physical functioning", "general health perception", "vitality", and "social functioning" domains after three months of intradialytic aerobic training.…”
Section: Quality Of Lifementioning
confidence: 96%
See 4 more Smart Citations
“…Those authors have justified their findings due to the small size of the sample and lack of routine physical exercise programs in dialysis centers, which can also explain some results of the research. On the other hand, Reboredo et al (2007) 10 have found a significant improvement in the "physical functioning", "general health perception", "vitality", and "social functioning" domains after three months of intradialytic aerobic training.…”
Section: Quality Of Lifementioning
confidence: 96%
“…In addition to the influence on the QOL, both dialysis and the disease itself interfere with almost all body systems (cardiovascular, immune, endocrine/ metabolic, 12,10,14,18 and muscle skeletal) 19 , the respiratory system being specifically the most impaired according to some authors. 3,6,12,14 The most commonly found pulmonary alterations are as follows: limitation to air flow; obstructive disorders; a reduction in pulmonary diffusion capacity; and a decrease in respiratory muscle endurance and strength.…”
Section: Repercussion Of An Intradialytic Physical Therapy Protocolmentioning
confidence: 99%
See 3 more Smart Citations